Integrated nutrient management in cotton-sunflower cropping system in the sandy loam soils of north India - Mahavishnan, K.; Prasad, Mangal; Bhanu Rekha, K. (Journal of Tropical Agriculture, 2006)
Two sets of field experiments were conducted during kharif and rabi seasons of 2002-’03 and 2003-’04 at New Delhi under irrigated conditions to formulate site-specific nutrient management strategies for cotton-sunflower cropping system. The kharif experiments on cotton consisted of eight treatments viz., 100% recommended dose of fertilizers (RDF; 60:30:30 N, P2O5 and K2O kg ha-1), 50% RDF, mung bean intercrop incorporation (MII), farm yard manure (FYM; 12 t ha-1), 50% RDF+MII, 50% RDF+FYM, 50% RDF+FYM+MII and control, and it was laid out in a randomized block design with three replications. For the succeeding sunflower crop (rabi), each cotton plot was subdivided into three, and 0, 50 and 100% RDF were applied adopting a split plot design. Highest values for seed cotton yield and NPK uptake were observed for the combined application of all three nutrient sources. Nutrient management of cotton also exerted a marked effect on seed yield and NPK uptake of the succeeding sunflower crop. However, direct application to sunflower had a more pronounced effect than the residual effects.